2017
DOI: 10.3390/ijms19010011
|View full text |Cite
|
Sign up to set email alerts
|

l-Acetylcarnitine: A Mechanistically Distinctive and Potentially Rapid-Acting Antidepressant Drug

Abstract: Current therapy of mood disorders has several limitations. Although a high number of drugs are clinically available, as of today, nearly two-thirds of individuals do not achieve full symptomatic remission after treatment with conventional antidepressants. Moreover, several weeks of drug treatment are usually required to obtain clinical effects, a limitation that has considerable clinical implications, ranging from high suicide risk to reduced compliance. The characteristic lag time in classical antidepressant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 98 publications
0
26
1
6
Order By: Relevance
“…ALC modulates the cholinergic system by increasing acetyl-CoA content and choline acetyltransferase activity. Moreover, it modulates GABAergic, dopaminergic and glutamatergic neurotransmitter systems ( Chapela et al, 2009 ; Nasca et al, 2013 ; Wang et al, 2014 ; Singh et al, 2016 ; Chiechio, Canonico & Grilli, 2017 ). In rats, ALC decreased the immobility time in the forced swim test and increased sucrose preference in 3 days of treatment, whereas 14 days were necessary to obtain the same effects with clomipramine ( Nasca et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALC modulates the cholinergic system by increasing acetyl-CoA content and choline acetyltransferase activity. Moreover, it modulates GABAergic, dopaminergic and glutamatergic neurotransmitter systems ( Chapela et al, 2009 ; Nasca et al, 2013 ; Wang et al, 2014 ; Singh et al, 2016 ; Chiechio, Canonico & Grilli, 2017 ). In rats, ALC decreased the immobility time in the forced swim test and increased sucrose preference in 3 days of treatment, whereas 14 days were necessary to obtain the same effects with clomipramine ( Nasca et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this molecule is widely consumed as a dietary supplement for physical exercise ( Ribas, Vargas & Wajner, 2014 ; Nicassio et al, 2017 ). Recently, preclinical and clinical studies have demonstrated the effects of ALC on parameters relevant to anxiety, schizophrenia, and mood disorders; with onset of action faster than antidepressant drug and exert neuroprotective, neurotrophic, and analgesic effects ( Levine et al, 2005 ; Wang et al, 2015 ; Traina, 2016 ; Singh et al, 2017 ; Nasca et al, 2017 ; Chiechio, Canonico & Grilli, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on published studies, we treated cortical PNs with the cell-permeant mitochondria modulator L-Carnitine (Dickey and Strack, 2011;Sainath et al, 2017), a cell-permeant, lysine-derived quaternary amine that acts by promoting the metabolism of long-chain fatty acids by the mitochondria. It has been shown to be neuroprotective in a wide variety of metabolic stresses (Tefera and Borges, 2016;Zanelli et al, 2005) and has clinical interest in the treatment of depression and anxiety (Chiechio et al, 2017;Filiou and Sandi, 2019). We achieved single-cell knockout of NUAK1 through EVCE of CRE-coding plasmid in NUAK1 F/F cortical PNs and quantified axon morphology at 5DIV.…”
Section: Upregulation Of Mitochondria Function Rescues Collateral Bramentioning
confidence: 99%
“…It is possible that (S)‐ketamine‐induced dopamine release relates to acute psychotomimetic side effects in humans. In addition to ketamine, other drugs 24‐26 and treatments 27‐29 can also produce rapid anti‐depressant‐like effects, but they are not long‐lasting. At present, mechanisms for the rapid anti‐depressant effects are not completely clear.…”
Section: Introductionmentioning
confidence: 99%